Seasonal variations of microbial community structure, assembly processes, and influencing factors in karst river - Guan, Xiangyu; He, Ruoxue; Zhang, Biao; Gao, Chengjie; Liu, Fei (Frontiers in Microbiology, 2023)
The physicochemical properties and microbial communities have significant annual and seasonal changes in karst aquifers. To explore the changes of microbial community and their relationships with environmental factors, water samples were collected from a typical karst river in January 2017 (Jan-2017), August 2017 (Aug-2017), August 2018 (Aug-2018) and January 2019 (Jan-2019), respectively. Microbial communities in winter (Jan-2017 and Jan-2019) were stable with high similarity in spite of the two years sampling interval, but the microbial communities in Aug-2017 was different from that in Aug-2018. In four sampling times, there were 275 shared genera, whose average relative abundance ranging from 89.04% to 96.27%. The winter and summer specific genera were mainly from the recharge of tributary site K6 and discharge of waste water treatment plant (K2 and K3), respectively. The deterministic processes had a more significant effect on the microbial community assembly in winter than that in summer, which was affected by environmental pressure from pollution. Furthermore, antibiotics and inorganic nitrogen pollution affected element cycles of nitrogen and sulfur indirectly through ecological modules in karst river, and the denitrification and desulfurization processes were potentially inhibited. These findings contributed to understand the changes and its assembly mechanism of microbial community, as well as the feedback to environment in polluted karst river.